Cell-intrinsic adaptation arising from chronic ablation of a key Rho GTPase regulator - Cerikan, Berati; Shaheen, Ranad; Colo, Georgina P.; Gläßer, Christine; Hata, Shoji; Knobeloch, Klaus-Peter; Alkuraya, Fowzan S.; Fässler, Reinhard; Schiebel, Elmar (Developmental cell, 2016)
Summary Genome-editing technologies allow systematic inactivation of human genes. Whether knockout phenotypes always reflect gene functions as determined by acute RNAi is an important question. Here we show how the acute knockdown of the Adams-Oliver syndrome (AOS) gene DOCK6, coding for a RAC1/CDC42 guanine nucleotide exchange factor, results in strikingly different phenotypes to those generated by genomic DOCK6 disruption. Cell-intrinsic adaptation compensates for loss of DOCK6 function. Prolonged DOCK6 loss impacts upon the MRTF-A/SRF transcription factor, reducing levels of the ubiquitin-like modifier ISG15. Reduced ISGylation of the IQGAP1 protein increases levels of active CDC42 and RAC1 to compensate for DOCK6 disruption. Similar downregulation of ISG15 in cells from DOCK6 AOS patients indicates that such adaptation can compensate for genetic defects during development. Thus, phenotypes of gene inactivation are critically dependent on the timescale, as acute knockdown reflects a transient state of adjustment to a new equilibrium that is attained following compensation.
Gesehen am 29.04.2020